EFEK FUNGSI RCC DALAM AUTENTIKASI CITRA BERWARNA BERBASIS TRANSFORMASI INTEGER - Wibawa, Helmi Arif (MATEMATIKA, 2010)
One method that can be used to authenticate the image is an integer transformation method. This method works on a single layer of color, so for the authentication process on a color image having more than one color layer, then the RCC function can be used to reduce existing color layer. For some cases, RCC function turns out to give a negative effect on the image authentication process and the quality of the image. This article discusses about the effect of the use of RCC functions in the process of image authentication. Testing is done by comparing the results between processes that use RCC functions and processes that do not use it. The parameters used are the values ​​saved bits, storage capacity, PSNR values ​​and ability to perform the authentication process